SHIFTING THE ROLE OF MEDIATION IN ISLAMIC INHERITANCE DISPUTES: AN OVERVIEW OF ISLAMIC LEGAL PHILOSOPHY - Adi Nur Rohman (Fakultas Hukum, Universitas Diponegoro, 2022)
This article aims to see the other side of mediation as an alternative settlement of inheritance disputes. The general view of the community is that mediation is carried out after the occurrence of a dispute as a form of dispute resolution between the disputing parties. However, the perspective of Islamic legal philosophy sees the other side of the role of mediation in dealing with disputes, including inheritance disputes. The writing of this paper is done in an analytical descriptive manner that combines a normative juridical approach with a philosophical approach. The study results show that the settlement of inheritance disputes can be done in two ways; litigation and non-litigation. As one of the non-litigation channels and acting as a dispute resolution institution, mediation also prevents disputes. Mediation is positioned to avoid disputes arising at the philosophical level in inheritance cases. This argument can be seen from the statements in the Qur'an and hadith regarding inheritance law which indicate that the existence of inheritance law is intended as an effort to prevent disputes.